Training on the Utilization of Mail Merge for Efficient Creation of RT Cover Letters in the Pasar Lama Urban Village Environment - Maulani, Jauhari; Ridho, Ihda Innar; Mahalisa, Galih; Amin, Muhammad; Firdaus, Muhammad Iqbal; Syafarina, Gita Ayu; Hijriana, Nadiya (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This research paper aims to explore the use of mail merge to improve administrative correspondence for the Heads of RT (Neighborhood Associations) and their staff in the Pasar Lama sub-district of Banjarmasin. It identifies challenges with current handwritten methods, such as inefficiency and disorganization, highlighting the importance of this study for enhancing community administrative services.Method: The study employs a qualitative approach through training sessions developed by the PKM team from Uniska. Data collection includes pre- and post-training assessments and participant feedback, focusing on the impact of mail merge on the efficiency and accuracy of letter creation.Practical Applications: The findings suggest that implementing mail merge can significantly reduce the time spent on correspondence, ensure consistent formatting, and improve record-keeping. These enhancements can serve as a model for other regions looking to modernize administrative processes and increase efficiency.Conclusion: In conclusion, this research demonstrates the benefits of mail merge for administrative correspondence, leading to greater efficiency and organization. The results underscore the necessity of modernizing communication methods to address current challenges in local governance.